GAMBARAN PERCOBAAN PENAMBAHAN EM-4 DAN AIR CUCIAN BERAS TERHADAP KECEPATAN PROSES PENGOMPOSAN - Wandhira, Ajeng Ayu; Mulasari, Surahma Asti (Jurnal Kesehatan Masyarakat, 2013)
ABSTRACT Background: The amount of organic waste every day increasing.Composting is a wise step to reduce the increase in the volume of organicwaste from households or industry. Useful addition to reducing the volume oforganic waste, composting can be beneficial in the economic andenvironmental aspects. This study used dry teak leaf litter and rice water aswell as EM-4 as bioactivator in composting. The goal was to determine theextent of the influence of rice water and EM-4 to speed the compostingprocess. Methods: Type of the research was qualitative with laboratorium test. Therewere four treatments, P1 (1 Kg dry teak leaves and rice water), P2 (1 Kg dryteak leaves and EM-4), P3 (1 Kg dry teak leaves, rice water and EM-4), andcontrol (1 Kg dry teak leaves and water wells) with each treatment includedthree replications. There are 4 indicators composting examined in this study,the temperature measured with a thermometer and color, surfaced measure,and the structure as measured by organoleptic testing by several people.Each of the indicators examined every 5 days. Results data were analyzedby descriptive qualitative. Results: There were differences in the speed of the composting process ateach treatment. Composting with rice water (P1) mature on day 90, compostwith EM-4 (P2) mature on day 55, compost with rice water and EM-4 (P3)mature on day 40, and compost with well water (control) is immature at day90.Conclusion: Compost with material 1 Kg dry teak leaves, EM-4, and ricewater faster than other compost. Keywords: Compost, composting, rice water, EM-4